Analysis of Risk Factors for Adjacent Segment Degeneration after Minimally Invasive Transforaminal Interbody Fusion at Lumbosacral Spine. (21st April 2022) - Dong, Shengtao; Li, Jie; Jia, Xiaomeng; Zhu, Jieyang; Chen, Yaoning; Yuan, Bo
Abstract : Background . Adjacent segment degeneration (ASD) has been considered as a serious complication from changes in the biological stress pattern after spinal fusion. The sagittal balance significantly associated with lumbar loading is largely dependent on L5-S1 segment. However, the evidence indicating risk factors for radiological and symptomatic ASD after minimally invasive transforaminal interbody fusion (MIS-TLIF) remains insufficient. Methods . This single-central retrospective study recruited patients with lumbosacral degeneration receiving MIS-TLIF at the L5-S1 level from January 2015 to December 2018. The targeted variables included demographic information, radiological indicators, surgery-related parameters, and patient-reported outcomes (PROs) extracted from the electronic medical system by natural language processing. In these patients, a minimum of 3-year follow-up was done. After reviewing the preoperative and postoperative follow-up digital radiographs, patients were assigned to radiological ASD group (disc height narrowing ≥3 mm, progressive slipping ≥3 mm, angular motion >10°, and osteophyte formation >3 mm), symptomatic ASD group, and control group. We identified potential predictors for radiological and symptomatic ASD with the service of stepwise logistic regression analysis. Results . Among the 157 consecutive patients treated with MIS-TLIF in our department, 16 cases (10.2%) were diagnosed with radiological ASD at 3-year follow-up. The clinical evaluation did not reveal suspicious risk factors, but several significant differences were confirmed in radiological indicators. Multivariate logistic regression analysis showed postoperative PI, postoperative DA, and ∆PI-LL in radiological ASD group were significantly different from those in control group. Nevertheless, for patients diagnosed with simultaneously radiological and symptomatic ASD, postoperative DA and postoperative PT as risk factors significantly affected the clinical outcome following MIS-TLIF. Conclusion . In this study, while approximately 10% of lumbosacral degenerations develop radiographic ASD, prognosis-related symptomatic ASD was shown not to be a frequent postoperative complication. Postoperative PI, postoperative DA, and mismatched PI-LL are risk factors for radiological ASD, and postoperative DA and postoperative PT are responsible for the occurrence of symptomatic ASD following MIS-TLIF. These radiological risk factors demonstrate that restoration of normal sagittal balance is an effective measure to optimize treatment strategies for secondary ASD prevention.